Relationship between academic administrator leadership styles and lecturer job satisfaction at Malaysian Research Universities - Sadeghi, Amir (2012)
Leadership style as a key factor affects subordinates job satisfaction, which in turn is essential for success of each organization. These factors are pivotal for organizational effectiveness. The main purpose of this research was to examine the relationship between heads of departments’ leadership styles and lecturers’ job satisfaction at Malaysian Research Universities (RUs). It was conducted in three Malaysian RUs including Universiti Kebangsaan Malaysia (UKM), Universiti of Malaya (UM), and Universiti Putra Malaysia (UPM). A quantitative method was employed to collect data A quantitative correlational method was employed to collect the data. The population of this study consisted of 3431 lecturers from three Malaysian Research Universities including professors,associate professors,senior lecturers, and lecturers (with the exceptions of tutors). In order to determine adequate sample size, the number of sample for each statistical analysis was calculated using GPower 3.1 statistical software and the largest sample size of 305 was then selected. In this study, the proportional stratified random sampling was used to ensure that an adequate number of subjects are chosen. ‘Multifactor Leadership Questionnaire Form 5x’ and ‘Wood’s Faculty Job Satisfaction/Dissatisfaction Scale’ were utilized to measure the perceived leadership styles of heads of departments and the lecturers’ job satisfaction, respectively. The responses were subjected to Independent sample t-test, one way ANOVA, Pearson product moment correlation coefficient, and stepwise multiple regression. The findings revealed that heads of departments in the RUs utilize a combination of transformational, transactional, and laissez-faire leadership styles. Inspirational motivation and contingent reward are dominant transformational and transactional leadership behaviors of heads of departments respectively. Lecturers enjoy moderate levels of intrinsic, extrinsic, and overall job satisfaction. They are more intrinsically satisfied which implies that lecturers are reliable human resource to contribute in development of the RUs. Regarding intrinsic satisfaction, the work itself and in terms of extrinsic satisfaction, interpersonal relations are the constructs which received the highest mean scores. Salary, and policy and administration are constructs of extrinsic satisfaction which received the lowest mean scores and need to be considered more by the RU policy makers. In terms of intrinsic, extrinsic,and overall satisfaction, male lecturers, lecturers with professorial academic rank, and lecturers aged 56 and above are more satisfied than their counterparts. The lecturers with doctorate degrees are more intrinsically satisfied compared to lecturers with master degrees. With respect to teaching experience, no significant differences can be observed among different groups. The study revealed that among three discernable leadership styles, the transformational and the transactional leadership styles were positively correlated with the lecturers’ job satisfaction, while laissez-faire was negatively correlated with the lecturers’ job satisfaction. The results regarding the strength of the relationship showed that the correlation between transactional and laissez-faire leadership styles and the lecturers’job satisfaction was weak, whilst transformational leadership style and job satisfaction were moderately correlated with each other. It also revealed that contingent reward is a multidimensional leadership construct which has both transformational and transactional characteristics. The study found empirical proof that lecturers are more likely to show higher levels of job satisfaction if they perceive that their heads of departments exhibit transformational leadership behaviors. Regression analysis indicated that transformational leadership and laissez-faire are significant predictors of overall satisfaction, and that transformational leadership is the dominant predictor. Based on the findings, it is recommended that the RU administrators increasingly employ transformational and decrease exhibition of laissezfaire leadership behaviors to enhance lecturers’job satisfaction. Leadership styles of heads of departments and lecturers’ job satisfaction are important factors for achieving the RUs’ goals; therefore, policy makers should utilize appropriate strategies to improve administrators’leadership knowledge and abilities and elevate level of lecturers’ job satisfaction. These are vital for future success of the RUs.